Evaluation of the energy and environmental impacts of zero- energy buildings (ZEB): literature review and state of the art - SEMASSOU, GUY CLARENCE (My University, 2021)
This study was supported financially by the Afro-German Network of Excellence in Science (AGNES), through the program "AGNES Intra-Africa Mobility Grant for Junior Researchers". Zero-energy buildings (BEZs) are considered an integrated solution for solving the problems of energy saving, reducing the environmental impact of buildings. NZEB might even be possible with electricity generation if enough renewable energy could be used. In addition, various building service systems using renewable energy sources have been widely considered for potential applications in NZEB. All these new features extend the technical limits of conventional energy-efficientbuildings. They also attach a deeper involvement to the sustainable development of building technology and therefore pose a challenge to the performance evaluation work of NZEB. This paper presents a literature review of the evaluation of NZEBs. An overview of NZEB definitions and energy efficiency measures is presented so that the research focus and technological limitations can be clarified for the NZEB assessment. Next, a summary of the commonly used research method, tool and evaluation performance indicator is provided for the methodologypart. This part also includes a discussion on the application of life cycle analysis (LCA) in the NZEB assessment and the role of LCA in promoting a well-defined NZEB. Finally, potential progress in NZEB assessment with possible development trends is highlighted in terms of energy storage, load matching and intelligent network.
Keywords: Net Zero energy building; Energy; efficiency; Renewble energy; Environmental impact; Life cycle analysis